Ocean acidification risk assessment for Alaska's fishery sector. (August 2015) - Mathis, J.T.; Cooley, S.R.; Lucey, N.; Colt, S.; Ekstrom, J.; Hurst, T.; Hauri, C.; Evans, W.; Cross, J.N.; Feely, R.A.
Graphical abstract: Highlights: The intensity, extent and duration of ocean acidification in the coastal areas around Alaska will increase. Important commercial and subsistence fisheries in Alaska are co-located where enhanced ocean acidification will occur. Coastal human communities in southeast and southwest Alaska are highly reliant on fishery harvests. Coastal human communities in southeast and southwest Alaska face the highest risk from ocean acidification. Abstract: The highly productive fisheries of Alaska are located in seas projected to experience strong global change, including rapid transitions in temperature and ocean acidification-driven changes in pH and other chemical parameters. Many of the marine organisms that are most intensely affected by ocean acidification (OA) contribute substantially to the state's commercial fisheries and traditional subsistence way of life. Prior studies of OA's potential impacts on human communities have focused only on possible direct economic losses from specific scenarios of human dependence on commercial harvests and damages to marine species. However, other economic and social impacts, such as changes in food security or livelihoods, are also likely to result from climate change. This study evaluates patterns of dependence on marine resources within Alaska that could be negatively impacted by OA and current community characteristics to assess the potential risk to the fishery sector from OA. Here, we used a risk assessment framework based on one developed by the Intergovernmental Panel on Climate Change to analyze earth-system global ocean model hindcasts and projections of ocean chemistry, fisheries harvest data, and demographic information. The fisheries examined were: shellfish, salmon and other finfish. The final index incorporates all of these data to compare overall risk among Alaska's federally designated census areas. The analysis showed that regions in southeast and southwest Alaska that are highly reliant on fishery harvests and have relatively lower incomes and employment alternatives likely face the highest risk from OA. Although this study is an intermediate step toward our full understanding, the results presented here show that OA merits consideration in policy planning, as it may represent another challenge to Alaskan communities, some of which are already under acute socio-economic strains.